2014
DOI: 10.1155/2014/862851
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Cost-Efficacy of Biologic Therapies for Moderate to Severe Psoriasis: A Meta-Analysis and Cost-Efficacy Analysis Using the Intention-to-Treat Principle

Abstract: Background. Compared to conventional therapies, biologics are more effective but expensive in treating psoriasis. Objective. To evaluate the efficacy and cost-efficacy of biologic therapies for psoriasis. Methods. We conducted a meta-analysis to calculate the efficacy of etanercept, adalimumab, infliximab, and ustekinumab for at least 75% reduction in the Psoriasis Area and Severity Index score (PASI 75) and Physician's Global Assessment clear/minimal (PGA 0/1). The cost-efficacy was assessed by calculating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…The included drug survival studies did not consider the costs of treatments. One previous study on the cost-efficacy of biologics for treating psoriasis demonstrates ustekinumab and adalimumab had the lowest 1-year cost per PASI 75 responder, while ustekinumab had the lowest 2-year cost per PASI 75 responder 46 . Clinicians may consider the data on drug survival and cost efficacy in choosing biologics for treating psoriasis to achieve clinical benefit at the least medical expenditure.…”
Section: Discussionmentioning
confidence: 91%
“…The included drug survival studies did not consider the costs of treatments. One previous study on the cost-efficacy of biologics for treating psoriasis demonstrates ustekinumab and adalimumab had the lowest 1-year cost per PASI 75 responder, while ustekinumab had the lowest 2-year cost per PASI 75 responder 46 . Clinicians may consider the data on drug survival and cost efficacy in choosing biologics for treating psoriasis to achieve clinical benefit at the least medical expenditure.…”
Section: Discussionmentioning
confidence: 91%
“…All studies provided a research question; however, the viewpoint of the analyses was stated clearly in only 77% [ 28 , 29 , 32 35 , 37 39 , 41 52 , 54 57 , 59 , 61 , 62 , 64 66 , 70 – 76 , 78 80 ]. A total of 47 studies reported the source of effectiveness estimates [ 28 42 , 48 79 ], and in nearly two-thirds of them, further information on methods of synthesis (if based on multiple studies) or design and result (if based on a single study) was provided [ 28 , 30 , 31 , 33 36 , 38 , 40 , 48 , 52 , 54 , 55 , 58 60 , 63 66 , 69 74 , 78 , 79 ]. Even though price data was always recorded, only 31 studies reported quantities of resources and unit costs separately [ 28 , 29 , 32 , 34 , 35 , 38 , 40 42 , …”
Section: Resultsmentioning
confidence: 99%
“…Ixekizumab was considered in one study. The majority of studies analyzed the economic relationship between the TNF-inhibitors adalimumab, etanercept, and infliximab (n = 32; 60%) [ 28 30 , 32 , 34 , 36 , 39 41 , 43 50 , 56 58 , 63 , 64 , 67 70 , 72 – 77 ] ( Fig 2B ). In all six studies investigating secukinumab, this medication was compared to ustekinumab ( Fig 2C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Somado a isto, o custo elevado dessa classe de fármacos constitui outro fator limitante de adesão ao tratamento, particularmente nos países em desenvolvimento (Chi, Wang, 2014;Diamantino, Ferreira, 2012).…”
Section: Psoríase E Tratamentos Farmacológicosunclassified